2003
DOI: 10.1128/iai.71.6.3485-3495.2003
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Antigenic Polymorphism in Plasmodium falciparum : Extensive Serological Cross-Reactivity between Allelic Variants of Merozoite Surface Protein 2

Abstract: Diversity in the surface antigens of malaria parasites is generally assumed to be a mechanism for immune evasion, but there is little direct evidence that this leads to evasion of protective immunity. Here we show that alleles of the highly polymorphic merozoite surface protein 2 (MSP-2) can be grouped (within the known dimorphic families) into distinct serogroups; variants within a serogroup show extensive serological crossreactivity. Cross-reactive epitopes are immunodominant, and responses to them may be bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 41 publications
5
55
1
Order By: Relevance
“…We also hypothesized that the crucial interactions for class switching were more likely to take place between MSP2 and T cells than between MSP2 and B cells, as following natural infection, human antibodies to MSP2 recognize predominantly dimorphic and polymorphic sequences, with little or no antibody to the conserved sequences being detectable (52), suggesting that there are no dominant B-cell epitopes within the highly conserved regions of the molecule. Furthermore, although conserved or cross-reactive epitopes for antibodies are present throughout the MSP2 molecule (24), dominant epitopes for human (41,53) and murine (40) T cells have been identified within the conserved sequences of MSP2. The data presented here essentially support these predictions in that (i) mice immunized with full-length MSP2 made little or no antibody to the conserved C terminus, (ii) we have identified a dominant T-cell epitope within the conserved C terminus of the molecule which is able to drive class switching to IgG2b, and (iii) this peptide is not, in itself, a major target for anti-MSP2 antibodies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We also hypothesized that the crucial interactions for class switching were more likely to take place between MSP2 and T cells than between MSP2 and B cells, as following natural infection, human antibodies to MSP2 recognize predominantly dimorphic and polymorphic sequences, with little or no antibody to the conserved sequences being detectable (52), suggesting that there are no dominant B-cell epitopes within the highly conserved regions of the molecule. Furthermore, although conserved or cross-reactive epitopes for antibodies are present throughout the MSP2 molecule (24), dominant epitopes for human (41,53) and murine (40) T cells have been identified within the conserved sequences of MSP2. The data presented here essentially support these predictions in that (i) mice immunized with full-length MSP2 made little or no antibody to the conserved C terminus, (ii) we have identified a dominant T-cell epitope within the conserved C terminus of the molecule which is able to drive class switching to IgG2b, and (iii) this peptide is not, in itself, a major target for anti-MSP2 antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Discrete domains of MSP2 were produced in E. coli as fusion proteins with the C-terminal region of GST (44) using the pGEX expression system (Amersham Pharmacia Bioscience, Little Chalfont, United Kingdom). The production and validation of proteins representing the dimorphic sequences of serogroup A (Di-A) and serogroup B (Di-B) and polymorphic sequences from each serogroup (Poly-A and Poly-B) have been described previously (24). Conserved 5Ј and 3Ј sequences of the MSP2 gene (Con-N], ϳ320 bp, and Con-C, ϳ325 bp) were amplified using specific primers (CN5Ј [CCAGTACCAGTAGGAGGC] and CN3Ј [GAAGAG AATTATATGAATATGGC]), ligated into pGEX-3, validated by DNA sequencing (44), and expressed in E. coli.…”
Section: Animals and Immunizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, it is clear that some adults in areas of endemicity produce a larger proportion of allele-specific antibodies (7,40), and these antibodies may provide selective advantages for some parasites. Previous studies with other malaria proteins (CSP and MSP2) have suggested that T-cell responses could be the source of immune selection pressure (15,16). While there is no clear evidence for AMA1, Polley and colleagues (40) proposed the possibility of selection pressures on AMA1 domain III by T-cell-mediated immunity.…”
Section: Vol 75 2007 Strain Specificity Of P Falciparum Ama1 Antibmentioning
confidence: 99%
“…Serum was eluted from filter papers as described by Corran et al (2008). Immunoglobulin G antibodies against blood stage antigens were determined by indirect enzyme-linked immunosorbent assay (indirect ELISA), as previously described (Drakeley et al, 2005) using recombinant MSP-119 (Wellcome Genotype), produced as previously described by Franks et al (2003) or recombinant AMA-1 (3D7). Briefly, flat bottom 96-well microtitre plates (Nunc, Roskilde, Denmark) were coated overnight with 50 μl of 0.5 mg/ml dilution of the specific antigen.…”
Section: Data Collectionmentioning
confidence: 99%